Characteristics of novel urban vegetation in two Portuguese urban regions - Pereira, Estevão (2022)
Urban novel ecosystems were sampled across vacant sites in two Portuguese urban regions. The flora were studied with a focus on species’ origin, life form, ecological, chorological and naturalisation types. A multivariate constrained ordination technique was used to identify relationships between plant composition and environmental factors. The vegetation of the two urban regions shows differences, highlighting biome influence, as well as due to climatic variables and (to a lesser degree) soil characteristics and lithology. Although native species are clearly dominant, the frequency of non-native species is high and most are potentially or effectively invasive. In the ecological spectrum, the dominance of opportunistic ruderal species suggests a risk of biotic homogenisation in these ecosystems, which is also noticeable in the analysis of life form, but less in chorological and nativeness spectra. Portuguese novel urban ecosystems are, therefore, simultaneously an opportunity, since spontaneous vegetation management is more cost effective and can bring wilderness to cities; and a hazard, because invasive species must be controlled to support biodiversity conservation efforts.